The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/cctc.202200484
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Alkylated Cobalt Catalyst for Photocatalytic H2 Generation in Liposomes

Abstract: Photocatalytic proton reduction is a promising way to produce dihydrogen (H 2 ) in a clean and sustainable manner, and mimicking nature by immobilising proton reduction catalysts and photosensitisers on liposomes is an attractive approach for biomimetic solar fuel production in aqueous solvents. Current photocatalytic proton reduction systems on liposomes are, however, limited by the stability of the catalyst. To overcome this problem, a new alkylated cobalt(II) polypyridyl complex (CoC 12 ) was synthesised an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“… a Liposome embedding a synthetic molecular CPQ triad, quinone and a F 0 -F 1 -ATP synthase for electron and proton transfer across the membrane with concomitant pH gradient generation coupled to the synthesis of ATP reported by A. Moore et al, 96 ( b ) proteoliposome embedding MtrCAB from S. oneidensis MR-1 and encapsulated N 2 O reductase for electron transfer across membrane with N 2 O-to-N 2 reduction reported by J. N. Butt et al, 58 ( c ) polymersome embedding donor and acceptor molecules at each domain of the membrane for transmembrane energy transfer reported by Y. Zheng, Y. Zhou et al, 119 ( d ) polymersome with embedded bacteriorhodopsin a F 0 -F 1 -ATP synthase for transmembrane proton transfer coupled to ATP synthesis reported by T. Vidaković-Koch et al, 99 ( e ) liposome containing a Ru-PS and a Ru-WOC for light-driven WO reported by L. Sun, B. König et al, 127 ( f ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by B. König et al, 132 ( g ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by S. Bonnet et al, 130 ( h ) liposome with a Ru-PS and a CoPc-CO 2 RC for light-driven CO 2 reduction to CO reported by L. Hammarström, E. Reisner et al, 93 ( i ) liposome with a HER-MOF embedded in the hydrophobic membrane and an encapsulated WO-MOF for overall light-driven WS reported by W. Lin, C. Wang et al 140 . …”
Section: Artificial Systems For Electron Proton and Energy Transfer A...mentioning
confidence: 94%
See 2 more Smart Citations
“… a Liposome embedding a synthetic molecular CPQ triad, quinone and a F 0 -F 1 -ATP synthase for electron and proton transfer across the membrane with concomitant pH gradient generation coupled to the synthesis of ATP reported by A. Moore et al, 96 ( b ) proteoliposome embedding MtrCAB from S. oneidensis MR-1 and encapsulated N 2 O reductase for electron transfer across membrane with N 2 O-to-N 2 reduction reported by J. N. Butt et al, 58 ( c ) polymersome embedding donor and acceptor molecules at each domain of the membrane for transmembrane energy transfer reported by Y. Zheng, Y. Zhou et al, 119 ( d ) polymersome with embedded bacteriorhodopsin a F 0 -F 1 -ATP synthase for transmembrane proton transfer coupled to ATP synthesis reported by T. Vidaković-Koch et al, 99 ( e ) liposome containing a Ru-PS and a Ru-WOC for light-driven WO reported by L. Sun, B. König et al, 127 ( f ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by B. König et al, 132 ( g ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by S. Bonnet et al, 130 ( h ) liposome with a Ru-PS and a CoPc-CO 2 RC for light-driven CO 2 reduction to CO reported by L. Hammarström, E. Reisner et al, 93 ( i ) liposome with a HER-MOF embedded in the hydrophobic membrane and an encapsulated WO-MOF for overall light-driven WS reported by W. Lin, C. Wang et al 140 . …”
Section: Artificial Systems For Electron Proton and Energy Transfer A...mentioning
confidence: 94%
“…The potential of artificial vesicles to develop compartmentalized systems for reductive transformations has also garnered substantial attention. In this context, liposome- and other membrane-based systems for photocatalytic HER 130 133 , CO 2 R 93 , 134 136 , and organic transformations 58 , 103 , have been reported.…”
Section: Compartmentalized Photocatalytic Systems For Her and Co ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This helps in understanding and improving, e.g., dye‐sensitized photocatalysis on surfaces, i.e., dye‐sensitized photoelectrochemical cells [ 1–4 ] or dye‐sensitized solar cells (DSSCs), [ 5–7 ] in light‐driven catalysis, [ 8,9 ] energy storage, [ 10–13 ] and biomimetic photocatalytic systems. [ 14–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…This helps in understanding and improving, e.g., dyesensitized photocatalysis on surfaces, i.e., dye-sensitized photoelectrochemical cells [1][2][3][4] or dye-sensitized solar cells (DSSCs), [5][6][7] in light-driven catalysis, [8,9] energy storage, [10][11][12][13] and biomimetic photocatalytic systems. [14][15][16][17][18] Within the context of light-driven hydrogen formation, pioneering work by Kiwi and Grätzel [19] and subsequently, Sakai and Ozawa [20] did show that the combination of light absorption, charge transfer, and storage of redox equivalents on viologen-type molecules rendered highly active photocatalytic systems. Covalent linkage between viologen electron acceptors and catalytically active metal centers led to an overall improvement of catalytic activity with respect to attainable turnover numbers and frequencies.…”
Section: Introductionmentioning
confidence: 99%